2024
DOI: 10.1038/s41467-024-46510-6
|View full text |Cite
|
Sign up to set email alerts
|

The chromatin factors SET-26 and HCF-1 oppose the histone deacetylase HDA-1 in longevity and gene regulation in C. elegans

Felicity J. Emerson,
Caitlin Chiu,
Laura Y. Lin
et al.

Abstract: SET-26, HCF-1, and HDA-1 are highly conserved chromatin factors with key roles in development and aging. Here we present mechanistic insights into how these factors regulate gene expression and modulate longevity in C. elegans. We show that SET-26 and HCF-1 cooperate to regulate a common set of genes, and both antagonize the histone deacetylase HDA-1 to limit longevity. HCF-1 localization at chromatin is largely dependent on functional SET-26, whereas SET-26 is only minorly affected by loss of HCF-1, suggestin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 71 publications
0
1
0
Order By: Relevance
“…HCF-1, which was first isolated from the human herpes simplex virus, is a transcriptional cofactor that regulates the indicated target gene transcription, such as the cell cycle regulatory proteins E2 promoter binding factors (E2Fs) [ 66 ], the maintenance of the embryonic stem cell pluripotency factor Ronin [ 67 ], and the regulatory proteins for glucose metabolism proliferator-activated receptor-gamma coactivator-1 (PGC-1) [ 68 ] and forkhead box O (FOXO) [ 69 ], which in turn are involved in the regulation of embryonic stem cell pluripotency, cell cycle progression, cell proliferation, and metabolic stress. Studies have shown that high expression of HCF-1 is a marker for poor prognosis in the treatment of malignancies such as primary prostate tumors, lymphomas, AML, and sarcoid lymphomas [ 70 ].…”
Section: Ogt/hcf-1 Complexmentioning
confidence: 99%
“…HCF-1, which was first isolated from the human herpes simplex virus, is a transcriptional cofactor that regulates the indicated target gene transcription, such as the cell cycle regulatory proteins E2 promoter binding factors (E2Fs) [ 66 ], the maintenance of the embryonic stem cell pluripotency factor Ronin [ 67 ], and the regulatory proteins for glucose metabolism proliferator-activated receptor-gamma coactivator-1 (PGC-1) [ 68 ] and forkhead box O (FOXO) [ 69 ], which in turn are involved in the regulation of embryonic stem cell pluripotency, cell cycle progression, cell proliferation, and metabolic stress. Studies have shown that high expression of HCF-1 is a marker for poor prognosis in the treatment of malignancies such as primary prostate tumors, lymphomas, AML, and sarcoid lymphomas [ 70 ].…”
Section: Ogt/hcf-1 Complexmentioning
confidence: 99%